The earliest evidence for upper paleolithic occupation in the Armenian Highlands at Aghitu-3 Cave - Kandel, Andrew W.; Gasparyan, Boris; Allué, Ethel (Journal of human evolution, 2017)
With its well-preserved archaeological and environmental records, Aghitu-3 Cave permits us to examine the settlement patterns of the Upper Paleolithic (UP) people who inhabited the Armenian Highlands. We also test whether settlement of the region between ∼39-24,000 cal BP relates to environmental variability. The earliest evidence occurs in archaeological horizon (AH) VII from ∼39-36,000 cal BP during a mild, moist climatic phase. AH VI shows periodic occupation as warm, humid conditions prevailed from ∼36-32,000 cal BP. As the climate becomes cooler and drier at ∼32-29,000 cal BP (AH V-IV), evidence for occupation is minimal. However, as cooling continues, the deposits of AH III demonstrate that people used the site more intensively from ∼29-24,000 cal BP, leaving behind numerous stone artifacts, faunal remains, and complex combustion features. Despite the climatic fluctuations seen across this 15,000-year sequence, lithic technology remains attuned to one pattern: unidirectional reduction of small cores geared towards the production of bladelets for tool manufacture. Subsistence patterns also remain stable, focused on medium-sized prey such as ovids and caprids, as well as equids. AH III demonstrates an expansion of social networks to the northwest and southwest, as the transport distance of obsidian used to make stone artifacts increases. We also observe the addition of bone tools, including an eyed needle, and shell beads brought from the east, suggesting that these people manufactured complex clothing and wore ornaments. Remains of micromammals, birds, charcoal, pollen, and tephra relate the story of environmental variability. We hypothesize that UP behavior was linked to shifts in demographic pressures and climatic changes. Thus, by combining archaeological and environmental data, we gain a clearer picture about the first UP inhabitants of the Armenian Highlands.